Entrevista a Nelson Manrique - Drinot, Paulo (Pontificia Universidad Católica del Perú, 2024)
In this interview, conducted in June 2023, historians Paulo Drinot and Nelson Manrique discuss the latter’s biography, historiographical production, political activism, university teaching and journalistic work. The interview opens a window on the life and work of one of the most important and influential intellectuals in Peru in the second half of the twentieth century and the beginning of the twenty-first century.

En esta entrevista, realizada en junio del 2023, los historiadores Paulo Drinot y Nelson Manrique conversan sobre la biografía, la producción historiográfica, la militancia política, la docencia universitaria, y la labor periodística, del segundo. La entrevista abre una ventana sobre la vida y obra de uno de los intelectuales más importantes e influyentes en el Perú de la segunda mitad del siglo XX y comienzos del siglo XXI.
Interview with Nelson Manrique
Keywords: Nelson Manrique; Historiography; Biography; The Peruvian Left; Nelson Manrique; Historiografía; Biografía; Izquierda peruana; https://purl.org/pe-repo/ocde/ford#6.01.01